Effect of Addition of Vegetable Oils on Rumen Fermentation and Methanogenesis under In Vitro Conditions - Mahajan, Chetna; Mangal, Kajal; Wadhwa, M. (Indian Journal of Animal Nutrition, 2018)
This study was conducted to assess the effect of vegetable oils (VOs) viz., cotton seed, sunflower seed and castor seed oil on rumen fermentation and methanogenesis by using in vitro gas production technique. The oils were supplemented to the complete feed (oats fodder and concentrate mixture in 60: 40 ratio) @ 1, 2 and 3% (DM basis). The supplementation of VOs did not affect net gas production (NGP), however, the digestibility of NDF and true OM as well as ME availability decreased (P<0.01) as compared to control group. It was the lowest in castor seed oil supplemented group supplied @ 2%. The methane production was the lowest (P<0.05) due to cotton seed oil supplementation at 1% level as compared to other vegetable oils but it increased (P<0.01) linearly with the level of VO supplementation. Total volatile fatty acids (VFAs) and acetate concentration increased up to 2% level while the propionate concentration reduced at all levels of VO supplementation. Total and individual VFAs production was the highest in the castor oil supplemented group. The optimum level of supplementation irrespective of the nature of oil was observed to be 1-2% on DM basis under in vitro conditions.